Study on Fluid Front Motion of Water, Nitrogen, and CO2 during Anisotropic Flow in Shale Reservoirs. (5th December 2022) - Zhang, Xiangxiang; Gu, Kai; Liu, Chengyu; Cao, Yangbing; Wang, J. G.; Gao, Feng
Abstract : The fluid front motion is an important phenomenon during anisotropic fluid flow in rock engineering. The pore pressure and mechanical responses may be significantly influenced and show an obvious difference near the moving fluid front. However, few studies have been conducted to investigate the front motion of different types of fluids during anisotropic fluid flow. In this work, a numerical model was proposed to detect the front motion of water, nitrogen, and CO2 in anisotropic shale reservoirs. The full coupling effects among mechanical deformation, fluid flow, and moving boundary in anisotropic porous media were considered in the model construction. The impacts of different fluid properties among water, nitrogen, and CO2 on the anisotropic fluid flow have been discussed. Then, the proposed model was applied to study the differences in front motion among different types of fluids in anisotropic shales. The impacts of permeability and mobility on fluid front motion were investigated. The theoretical equations for predicting the fluid front motion of different types of fluids were established by introducing corresponding correction coefficients to the previous formulas. The results showed that the model can well describe the anisotropic fluid permeation process. The fluid front motion increased with the increase of permeability and mobility. At the same permeability or mobility, the nitrogen front motion was the largest and the water front motion was the smallest. The difference in fluid front motion among water, nitrogen, and CO2 was caused by the difference of their viscosity and compressibility. The proposed formulas can fast and accurately predict the evolution of fluid front motion for different types of fluids.